2008
DOI: 10.1128/jvi.01413-07
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Acute Anti-Friend Virus CD8+T-Cell Responses by Coinfection with Lactate Dehydrogenase-Elevating Virus

Abstract: Friend virus (FV) and lactate dehydrogenase-elevating virus (LDV) are endemic mouse viruses that can cause long-term chronic infections in mice. We found that numerous mouse-passaged FV isolates also contained LDV and that coinfection with LDV delayed FV-specific CD8 ؉ T-cell responses during acute infection. While LDV did not alter the type of acute pathology induced by FV, which was severe splenomegaly caused by erythroproliferation, the immunosuppression mediated by LDV increased both the severity and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(139 citation statements)
references
References 70 publications
7
128
4
Order By: Relevance
“…It has also become clear that FV stocks used in the previous studies were contaminated with LDV, which compromises CD8 + T cell responses (27). To thoroughly investigate the potential factors that influence the onset of virus-specific CD8 + T cell responses following FV infection in the absence of LDV, we compared the Agspecific CD8 + T cell responses elicited by FV infection or injection of FBL3 tumor cells, a highly immunogenic murine leukemia cell line induced in a B6 mouse by F-MuLV (39).…”
Section: Fv Infection Results In the Generation Of Excessively Activamentioning
confidence: 99%
See 2 more Smart Citations
“…It has also become clear that FV stocks used in the previous studies were contaminated with LDV, which compromises CD8 + T cell responses (27). To thoroughly investigate the potential factors that influence the onset of virus-specific CD8 + T cell responses following FV infection in the absence of LDV, we compared the Agspecific CD8 + T cell responses elicited by FV infection or injection of FBL3 tumor cells, a highly immunogenic murine leukemia cell line induced in a B6 mouse by F-MuLV (39).…”
Section: Fv Infection Results In the Generation Of Excessively Activamentioning
confidence: 99%
“…One question is whether virus-specific CD8 + T cells contribute to the early control of FV in vivo. Although previous studies demonstrated that the depletion of CD8 + T cells significantly accelerated the acute splenomegaly (65)(66)(67), the FV stock used in these studies had been contaminated with LDV, a potent suppressor of CD8 + T cell responses (27). Using the LDV-free FV stock, we confirmed an exacerbated acute splenomegaly in CD8 + T cell-depleted animals upon FV infection (S. Takamura, S. Tsuji-Kawahara, and M. Miyazawa, unpublished observations), which seems to conflict with our current observations regarding the early loss of FV-specific CD8 + T cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(B10 × A.BY) F1 mice (Th1.2) were chronically infected with 1,500 spleen focus-forming units of FV/lactate dehydrogenaseelevating virus as described (45) and then adoptively transferred with 10 6 Thy1.1 CD8 + T cells from virus-specific TCR Tg mice (15). Seven days after adoptive transfer, Thy1.1 donor cells were sorted from the spleen using a FACSAria cell sorter (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…injection of 1500 spleen focus-forming units of uncloned virus stock containing B-tropic F-MuLV and polycythemia-inducing spleen focus-forming virus. As previously described, the FV complex also contains lactate dehydrogenase-elevating virus (4,22). Mice were considered chronically infected at 8 wk postinfection.…”
Section: Virus and Infectionsmentioning
confidence: 99%